2006
DOI: 10.1142/s0129083506000800
|View full text |Cite
|
Sign up to set email alerts
|

Particle Induced X-Ray Emission Studies of Anti-Diabetic Medicinal Plants

Abstract: Selected number of anti-diabetic medicinal plant leaves has been characterized by accelerator based particle-induced X-ray emission (PIXE) technique. Validity of the technique was assured by analyzing certified plant reference materials (CRMs). A large number of trace elements like Ti , V , Cr , Mn , Fe , Co , Ni , Cu , Zn , Rb , Sr and Pb are found to be present in these studied leaf samples with variable proportions. The concentrations of elements like K and Ca are quantified in percentage level whereas othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Rubidium is detected in one sample, P. posumba Bach. The concentrations are in agreement with those reported for other plant species [1,[4][5][6][7]12]. From Table 1, it is seen that the concentrations of the elements vary from one sample to another.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Rubidium is detected in one sample, P. posumba Bach. The concentrations are in agreement with those reported for other plant species [1,[4][5][6][7]12]. From Table 1, it is seen that the concentrations of the elements vary from one sample to another.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, the investigations of the trace element metabolism of human beings, animals and plants were and still remain a fascinating field of actual research. The possibility of relating trace element contents to the curative property possess by various medicinal plants is especially attractive in this interdisciplinary field and it has been quite widely studied by different authors [4][5][6]. …”
Section: Introductionmentioning
confidence: 99%
“…Much research has been done on organic aspect of plants in curing diseases, while little attention has been paid on the elemental composition of the plants. Most of these plants are found to be rich in one or more individual elements, thereby providing a possible link to the therapeutic action of the medicinal property of these plants [2,3]. Hence, the quantitative estimation of the concentration of various trace elements is important for determining the effectiveness of the medicinal plants in treating various diseases and/or in understanding their pharmacological action.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies [2,[5][6][7] have reported trace element contents of various medicinal plants by studying different plant parts. But there are no data particularly available on the trace element content of the different part samples of T. cordifolia, M. oleifera, and P. niruri.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 . Hence, further studies especially on these plants with respect to various conditions like the place where they grow, the climatic conditions, age, soil, water, etc.…”
Section: Resultsmentioning
confidence: 99%